Experimental model of intracranial hypertension with continuous multiparametric monitoring in swine - Andrade,Almir Ferreira de (2013)
Objective Intracranial hypertension (IH) develops in approximately 50% of all patients with severe traumatic brain injury (TBI). Therefore, it is very important to identify a suitable animal model to study and understand the pathophysiology of refractory IH to develop effective treatments. Methods We describe a new experimental porcine model designed to simulate expansive brain hematoma causing IH. Under anesthesia, IH was simulated with a balloon insufflation. The IH variables were measured with intracranial pressure (ICP) parenchymal monitoring, epidural, cerebral oximetry, and transcranial Doppler (TCD). Results None of the animals died during the experiment. The ICP epidural showed a slower rise compared with parenchymal ICP. We found a correlation between ICP and cerebral oximetry. Conclusion The model described here seems useful to understand some of the pathophysiological characteristics of acute IH.